2017
DOI: 10.1128/aac.01368-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Innate Immune Modulator Acitretin as a Strategy To Clear the HIV Reservoir

Abstract: The persistence of HIV despite suppressive antiretroviral therapy is a major roadblock to HIV eradication. Current strategies focused on inducing the expression of latent HIV fail to clear the persistent reservoir, prompting the development of new approaches for killing HIV-positive cells. Recently, acitretin was proposed as a pharmacological enhancer of the innate cellular defense network that led to virus reactivation and preferential death of infected cells. We evaluated the capacity of acitretin to reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Cell death was driven by RIG-I-mediated increases in the pro-apoptotic protein Bax, which can trigger caspase-mediated apoptosis (Li et al, 2016). Unfortunately, these findings were not replicated in a subsequent study that also evaluated latently infected cells lines and patient derived cells (Garcia-Vidal et al, 2017). …”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 95%
“…Cell death was driven by RIG-I-mediated increases in the pro-apoptotic protein Bax, which can trigger caspase-mediated apoptosis (Li et al, 2016). Unfortunately, these findings were not replicated in a subsequent study that also evaluated latently infected cells lines and patient derived cells (Garcia-Vidal et al, 2017). …”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 95%
“…Furthermore, the RIG-I agonist acitretin, an FDA-approved retinoic acid derivative, was recently shown to reactivate latent HIV and induce the selective apoptosis of latently HIV infected cells in vitro (21). However, a subsequent study that evaluated acitretin as an LRA in latently infected cell lines and patient-derived samples failed to extend these observations (22). A recent study demonstrated that the STING agonists 2=3=-cGAMP and cyclic di-AMP were able to decrease the amount of simian immunodeficiency virus (SIV) Gag in the DNA of peripheral blood mononuclear cells (PBMCs) obtained from monkeys exhibiting natural SIV control at 40 weeks postinfection (23).…”
mentioning
confidence: 99%
“…We observed parallels in CD4 + T cells from RA-stimulated cultures where the apoptosis marker CD10 was elevated in α4β7 expressing effector and TEMRA cells. Future studies are required to understand and validate the interdependence between α4β7 expression, RIG-1 signaling and stability of the viral reservoir as some study groups argue that Acitretin does not cause optimal activation and subsequent apoptosis of latently-infected cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%